MOB MENTALITY; GOOD GOVERNANCE AND THE RISING TREND OF MOB JUSTICE IN PAKISTAN; SOCIAL AND PSYCHOLOGICAL PERSPECTIVES - Muhammad Fayyaz Khokhar; Professor Liu Bangfan; Tayyaba Zia (International Journal of Contemporary Issues in Social Sciences, 2024)
In any community, mob justice—also referred to as “mob lynching,” “mob action,” or “jungle justice”—is a precursor of societal injustice. In recent years, mob/street justice violence has dramatically increased and has become a typical occurrence in Pakistan. It is now a standard procedure and a recognized method of handling and reacting to criminal situations, such as armed robbery, abduction, pickpocketing, theft, rape, etc. These outbursts of society are generally triggered once the masses lose their faith and hope in government, judicial system and law enforcement agencies. It is a well-established fact that such emotional outbursts and frustrations have deep-rooted psychological reasons like economic and social disparity. These factors force the masses to defy the laws and resort to uncivilized acts. Intricate access to justice, corruption and lengthy judicial proceedings are major attributes which cause discontent in the community; these factors once coupled with economic disparity, engender feelings of deprivation and hopelessness which results in lawlessness and anarchy. This study intends to analyze the rising trend of mob mentality/violence, and its impact on our society and identify the ways and means to prevent this trend in Pakistani society. In Pakistan, mob justice has become more prevalent. People’s lack of faith in the formal criminal justice system is a reflection of the sad reality. The study is of vital importance to comprehend the factors responsible for mob violence and how to curb it.